Political inequality - Ansell, B; Gingrich, J (Oxford University Press, 2024)
The rise of economic inequality in the UK over the past four decades raises serious questions about the state of political equality in Britain. In this article, we analyse changes in political equality from voter participation to voting behaviour to the descriptive and substantive representativeness of Parliament. We find that voter participation in the electoral process has become substantially more unequal since the 1960s but that traditional geographic patterns of voting, where wealthier constituencies typically voted Conservative, have almost entirely vanished. Descriptively, Parliament has become more reflective in demographic and socio-economic terms of the population. In terms of substantive representation, policymaking in Britain has been more responsive to the interests of older homeowners than younger, less wealthy groups. Almost all British citizens nonetheless feel less represented by politicians and policymaking than they did several decades ago.